2019
DOI: 10.1093/rheumatology/kez571
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound B-lines and serum KL-6 correlate with the severity of idiopathic inflammatory myositis-associated interstitial lung disease

Abstract: Objective Idiopathic inflammatory myositis-associated interstitial lung disease (IIM-ILD) significantly increases morbidity and mortality. Lung ultrasound B-lines and Krebs von den Lungen-6 (KL-6) are identified as new sonographic and serum markers of ILD, respectively. The aim of our work was to assess the role of B-lines and KL-6 as markers of the severity of IIM-ILD. For this purpose, the correlation among B-lines score, serum KL-6 levels, high-resolution CT (HRCT) score, and pulmonary fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Imaging results were quantified and scored, and a comparative analysis of the values at baseline and at 52 weeks showed that KL-6 and SP-A were positively correlated with the CT scores in the aggravation group. Wang et al [ 46 ] and AI-Salmi et al [ 47 ] proposed that serum KL-6 and SP-A were related to HRCT and could be used as indicators for evaluating the progression of ILD. This is consistent with the findings of this study in patients with IPAF.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging results were quantified and scored, and a comparative analysis of the values at baseline and at 52 weeks showed that KL-6 and SP-A were positively correlated with the CT scores in the aggravation group. Wang et al [ 46 ] and AI-Salmi et al [ 47 ] proposed that serum KL-6 and SP-A were related to HRCT and could be used as indicators for evaluating the progression of ILD. This is consistent with the findings of this study in patients with IPAF.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, comprised of 60 confirmed CTD-ILD patients, including 11 patients with RA-ILD, circulating KL-6 levels correlated positively with the LUS B-line score ( r = 0.54, p < 0.0001) [ 17 ]. The significant relationship was confirmed in 38 patients with IIM-ILD ( r = 0.43, p < 0.01) [ 18 ]. In a recent case, B-lines and KL-6 were utilized to closely detect and follow a patient with anti-MDA-5-positive, clinically amyopathic dermatomyositis associated with rapidly progressive ILD [ 79 ].…”
Section: Review Of Relevant Medical Literaturementioning
confidence: 91%
“…In the past decade, lung ultrasound (LUS) B-lines and serum Krebs von den Lungen-6 antigen (KL-6) have been recognized as possible novel sensitive biomarkers to detect CTD-ILD [ 14 16 ]. In addition, a significant correlation between B-line number and serum KL-6 level was demonstrated recently in patients with CTD-ILD and idiopathic inflammatory myositis–related ILD (IIM-ILD) [ 17 , 18 ]. Based on this background, we believe it might be helpful to integrate LUS and KL-6 to screen and follow up RA patients with ILD.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence demonstrates that most cases of COVID-19 pneumonia correspond to interstitial lung disease. Previous studies have shown that the number of B-lines is strongly associated with HRCT severity score, pulmonary function test parameters, and serum biomarker KL-6 levels in connective tissue disease-associated interstitial lung disease (CTD-ILD) (18)(19)(20). In this pilot study, total B-lines score of LUS and semi-quantitative score of HRCT denoted sonographic and radiological severity, respectively.…”
Section: A B a Bmentioning
confidence: 99%
“…A proportion of COVID-19 patients will progress to develop pneumonia, which is significantly associated with worse prognosis and higher mortality (2,3). The mechanism leading to acute lung injury in COVID- 19 has not yet been fully elucidated. Until now, Chest computed tomography (CT) has been a pivotal diagnostic tool for COVID-19 pneumonia, which can identify early lung inflammation, stratify patients based on imaging manifestations, and closely follow up pulmonary lesion modification (2,3).…”
Section: Introductionmentioning
confidence: 99%